Metal-Free Radical Cyclization of Vinyl Isocyanides with Alkanes: Synthesis of 1-Alkylisoquinolines - Xue, Dengqi; Xue, Yijie; Yu, Haihua; Shao, Liming (Synthesis, 2019)
A metal-free radical cyclization reaction of vinyl isocyanides with alkanes is developed, allowing convenient access to a diverse range of potentially valuable 1-alkylisoquinolines. The methodology is simple and efficient, demonstrating excellent functional group tolerance and broad substrate scope. A mechanism involving a radical process is supported by kinetic isotope effect and radical inhibition studies.
Keywords: metal-free; radical cyclization reaction; vinyl isocyanides; alkanes; 1-alkylisoquinolines